2013
DOI: 10.1155/2013/610393
|View full text |Cite
|
Sign up to set email alerts
|

The Role ofKlebsiellain Crohn’s Disease with a Potential for the Use of Antimicrobial Measures

Abstract: There is a general consensus that Crohn's disease (CD) develops as the result of immune-mediated tissue damage triggered by infections with intestinal microbial agents. Based on the results of existing microbiological, molecular, and immunological studies, Klebsiella microbe seems to have a key role in the initiation and perpetuation of the pathological damage involving the gut and joint tissues in patients with CD. Six different gastroenterology centres in the UK have reported elevated levels of antibodies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 71 publications
(72 reference statements)
2
17
0
Order By: Relevance
“…3B , are Klebsiella pneumonia , Campylobacter hominis , and two species of Bifidobacter. Klebsiella pneumonia and Campylobacter hominis are potent pro-inflammatory agents: Klebsiella has been show to play a major role in the initiation of inflammation in IBD 43 , and Campylobacter is a common cause of severe gastroenteritis. The two species of Bifidobacter may serve to protect the gut mucosa through inhibition of NF κ B 44 , and upregulation of these anti-inflammatory species in IBD is consistent with data from patient fecal samples showing increased populations of probiotics such as Bifidobacterium and Lactobacillus 45 .…”
Section: Resultsmentioning
confidence: 99%
“…3B , are Klebsiella pneumonia , Campylobacter hominis , and two species of Bifidobacter. Klebsiella pneumonia and Campylobacter hominis are potent pro-inflammatory agents: Klebsiella has been show to play a major role in the initiation of inflammation in IBD 43 , and Campylobacter is a common cause of severe gastroenteritis. The two species of Bifidobacter may serve to protect the gut mucosa through inhibition of NF κ B 44 , and upregulation of these anti-inflammatory species in IBD is consistent with data from patient fecal samples showing increased populations of probiotics such as Bifidobacterium and Lactobacillus 45 .…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the dominance of Klebsiella following ampicillin exposure is noteworthy because, in humans, Klebsiella oxytoca has been identified as the causative organism for antibiotic-associated hemorrhagic colitis ( Högenauer et al, 2006 ). Klebsiella also has a key role in the initiation of pathological damage in patients with Crohn’s disease ( Rashid et al, 2013 ). Various studies have suggested that commensal organisms, such as Enterococcus and Klebsiella species, drive the pathogenesis of experimental intestinal inflammation and human IBD ( Sartor, 2006 , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strain-specific genes associated with Th1 cell induction are predicted to encode hemolysin-coregulated protein and enzymes involved in fructose-, galactitol-, mannose-, and long-chain fatty acidrelated uptake and metabolic pathways. Furthermore, the ability of pathobionts to outgrow other bacteria in the inflamed gut is supported by sequencing data, in which Klebsiella species and other bacteria associated with the oral cavity are more abundant in the guts of IBD patients compared to controls 28,88,89 . Klebsiella species are also more abundant in mouse models and human cohort studies of other gut diseases 90,91 .…”
Section: Microbial Strains Implicated In Ibdmentioning
confidence: 95%